(untitled) (Revista de Artes Marciales Asiáticas, 2012)
In recent years the Soviet born martial art of sambo has become increasingly well known in martial art circles. This is largely due to the success of sambo fighters in various mixed martial art venues. Offered here is a brief description of sambo’s development as well as a delineation of one of sambo’s hallmark strategies: offensive rolling. Examples of proper forward rolling and three related offensive techniques are presented. This paper provides a brief introduction to sambo’s history and one of its key tactical philosophies.